(untitled) (Research, Society and Development, 2020)
The sexuality is inserted in the physiotherapist actuation context considering its work subject, therefore deserves attention about the practical clinic challenges facing its patient’s sexuality. The objective of this research is to evaluate the physiotherapist`s knowledge and comfort about the human sexuality. The quantitative research, with convenience samples, composed of Rio Grande do Sul professionals. The tools to be applied were a socio-demographic questionnaire developed by the authors and the scale of knowledge, comfort and attitudes of physiotherapy students towards human sexuality (SKCAPS), sent to the professionals by e-mail. Attended this research 324 physiotherapists. The mean results from the SKCAPS evaluation shows that the professionals reported having good knowledge about sexuality issues (28,84±6,85), feel very comfortable to start a conversation about sexuality (34,55±8,48) but referring to discomfort, the professionals feel high unease (22,81±4,42) in different situations involving the patient sexuality. The physiotherapist considered having knowledge about themes involving sexuality, however, they still lack readiness about the approaches in assistances with situations of embarrassment to assist with quality their patients.